PENGARUH BAKTERI INDEGENOUS DALAM DEGRADASI SENYAWA FISIKA KIMIA LIMBAH BATIK DAN TEXTIL - Heri Ariadi; Linayati Linayati; Tri Yusufi Mardiana (JURNAL LITBANG KOTA PEKALONGAN, 2022)
The purpose of this study was to evaluate the effect of indigenous bacteria on the degradation process of physicochemical compounds in batik and textile wastewater. Research Methods: The method used in this study is a laboratory-scale experimental design and active participation involving batik business groups as partners. The data analyzed in this study were physical and chemical parameters of wastewater treated with bacterial isolates and aeration of 2-3 mg/L for 24 hours using an aerator blower compare with a capacity of 500 volts. The data were then analyzed descriptively quantitatively and qualitatively. The results showed that native bacteria significantly affected the decrease in pH and temperature parameters in batik waste, namely pH from 6.6 to 6.3, temperature from 29.470C to 28.200C. The results also showed a decrease in water chemical parameters which included BOD from 8.49 mg/L to 7.52 mg/L, COD from 5.52 mg/L to 4.40 mg/L, TSS from 272 mg/L to 187 mg/L, organic matter from 110 mg/L to 91 mg/L and increased dissolved oxygen capacity from 2.28 mg/L to 3.40 mg/L. Exactly the same conditions also occurred in textile waste samples, where the treatment of indigenous bacteria affected the decrease in pH parameters (6.8 to 6.7), temperature (28.670C to 28.010C), BOD (7.89 mg/L to 6 .11 mg/L). ), COD (12 to 9.5 mg/L), TSS (571.11 to 498.89 mg/L), organic matter (145 mg/L to 117 mg/L) and increased dissolved oxygen capacity of wastewater from 2 .83 mg/L to 4.01 mg/L. The conclusion of this study is that the application of native bacteria quantitatively greatly affects the rate of degradation of the physical and chemical parameters of batik and textile wastewater by 10-30% through the process of degradation of waste compounds for 24 hours. So that the treatment of indigenous bacterial isolates is considered quite effective when compared to no treatment.  Keywords: Organic matter, indigenous bacteria, wastewater, waters, pH